Manajemen Bisnis Bagi Pengelola BUMDes Kabupaten Pandeglang - Abdurrohman; Anis Fuad Salam; Dwi Fitrianingsih; Indar Riyanto; M, Atep Effiana Taufik (Universitas Serang Raya, 2021)
The purpose of this service is to convey knowledge and abilities in managing business for the BUMDES manager of Pandeglang Regency. This activity is carried out in order to help solve problems for BUMDES managers in carrying out business management. Before the community service activities take place, discussions were held with the Pandeglang District Community Empowerment and Village Administration (DPMPD) Office in relation to the problems faced by the BUMDES managers which would later be contained in the form of training materials organized by DPMPD Pandeglang Regency in collaboration with the College of Economics (STIE) ) Banten. The form of this community service activity is training on various materials related to problems in BUMDES, namely (1) BUMDES Success Road Map, (2) Entrepreneurship, (3) Leadership, (4) Marketing, (5) Cooperation, and (6) Governance BUMDES finances attended by 50 BUMDES managers selected by DPMPD Pandeglang Regency. In the implementation of training materials, the practices of how to lead, market, make cooperation and practice financial bookkeeping are inserted. Furthermore, to further strengthen the material in the final session, questions and answers and discussions were opened. Suggestions from this activity are the need for further assistance in the field and control of the implementation of BUMDES management activities.